MANAGEMENT OF SEXUAL VIOLENCE - Távara Orosco, Luis (2015)
Gender based violence is related to the power imbalance between men and women that is present, to a greater or lesser degree, in all societies. It was almost recently recognized as a human rights problem by the United Nations. It includes emotional, physical and sexual violence. Sexual violence is the extreme form of gender violence, usually accompanied by the other types of violence. Its prevalence is difficult to determine, but it most probably affects at least one third of women sometime in their life. It has multiple consequences over women’s physical and gynecological health, which greatly depends on the quality of care the woman received immediately after the assault. Unfortunately, most emergency health services, including those in women’s hospitals, are rarely prepared to provide correct care to these women. Care should be  multidisciplinary and involves crisis treatment, meticulous clinical examination and complementary auxiliary methods, treatment of physical lesions, prevention of pregnancy and of transmission of sexually transmitted infections and AIDS, and follow up for at least six months after the aggression.